SIWO MEGOU: KOREOGRAFI SIGER PEPADUN LAMPUNG - Luthfi Guntur Eka Putra (Institut Seni Indonesia Yogyakarta, 2020)
Siwo Megou merupakan karya tari yang berpijak pada gerak dasar tari Cangget Lampung. Karya ini terinspirasi dari kehidupan masyarakat Lampung. Siwo Megou diambil dari bahasa Lampung yang artinya Sembilan Marga. Kesembilan marga tersebut diikat oleh aliran sungai yang mengikat daerah tersebut. Kesembilan marga disatukan oleh ‘alat’ pemersatu yaitu siger pepadun. Kesembilan marga direpresentasikan ke dalam bentuk sebuah siger pepadun sebagai simbol persatuan. Musik yang digunakan berangkat dari tabuhan tradisi Lampung yang dikomposisi sesuai kebutuhan dan interpretasi penata. Karya ini ditarikan oleh sepuluh penari, sembilan lakilaki dan satu perempuan. Menggunakan rangsang kinestetik dan rangsang ideasional. Desain dramatik dibagi menjadi tiga segmen. ABSTRACT Siwo Megou is a dance work based on the basic movements of Cangget Lampung dance. This work is inspired by the life of the people of Lampung. Siwo Megou is taken from the Lampung language, which means the Nine Clans. The nine clans are bound by a river that binds the area. The nine clans are united by a unifying tool, the Siger Pepadun. The nine clans are represented in the form of a siger pepadun as a symbol of unity. The music used departed from the wasp of the Lampung tradition which was composed according to the needs and interpretation of the stylist. The theme used is unity. Dance works are danced by ten dancers, nine men and one woman. Using kinesthetic stimuli and professional stimuli. The dramatic design is divided into three segments according to the needs of this work.The discovery of motion in this work is the discovery of new motion according to the work requirements of this work. Motion motives obtained are then processed according to the creativity and interpretation of the stylist. The work of Siwo Megou's choreography arranged and danced in groups is a creation that is divided into three segments staged in the prosecenium stage on May 21, 2019.